2009
DOI: 10.1016/j.otohns.2008.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaires to evaluate anxiety and depressive levels in tinnitus patients

Abstract: If a patient reports a THI greater than 38, the otolaryngologist should supplement diagnostic studies with a psychological consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 16 publications
10
56
0
6
Order By: Relevance
“…A strong correlation resulted between THI scores and presence of anxiety/depression symptoms. This finding is in agreement with earlier studies reported in literature 37,38 . The results support the view that there is a connection between tinnitus and psychiatric disorders.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A strong correlation resulted between THI scores and presence of anxiety/depression symptoms. This finding is in agreement with earlier studies reported in literature 37,38 . The results support the view that there is a connection between tinnitus and psychiatric disorders.…”
Section: Discussionsupporting
confidence: 94%
“…When this reaction does not create any relief, the individual submerges into a depressive state in which the subject is conscious of his/her inability to confront that stimulus. Similar findings have also been reported by Crocetti et al 38 This attracts a heightened concern in the Indian context as there are no adequate tinnitus specialty clinics for detailed assessment and providing treatment with a systematic approach such as tinnitus retraining therapy.…”
Section: Discussionsupporting
confidence: 84%
“…Some people distressed by their tinnitus report symptoms of depression and anxiety, such as sleep disturbance, difficulty concentrating, fatigue, irritability, and even suicidal ideation [25][26][27]. Psychological techniques had already been developed and used with patients who experience tinnitus.…”
Section: Cognitive-behavioral Therapymentioning
confidence: 99%
“…This scale is composed of 25 questions and the scores can vary between 0 and 100. The THI specifies different ranges of an index score, namely light (0-16), mild (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), moderate (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), severe (58-76) and catastrophic (78-100) handicap. Cronbach's alpha was .92 indicating very good internal consistency, comparable to the original version of the THI [22].…”
Section: Methodsmentioning
confidence: 99%
“…In a next step, the total sample was divided into two subgroups: a group with slight/mild tinnitus severity (THI score < 38) and a group with moderate, severe or catastrophic tinnitus severity (THI score ≥ 38) [30]. Again the THI was correlated with the four indices for influence of prime types (happy, sad, fearful, angry face).…”
Section: The Relation Between Affective Priming Indices (Happy Sad mentioning
confidence: 99%